Selection and application of graphical and numerical statistical tools by prospective primary school teachers - Fernandes, José António (2019)
Teaching statistics in the early years requires that teachers at this school level develop skills to analyze small collections of data. Given a collection of quantitative data (12 observations), in this paper we looked at how students and prospective primary school teachers select and make appropriate graphs and identify and determine statistical measures suitable for summarizing the data, including the interpretation of the third quartile. The study involved 50 students who were attending the 2nd year of the Basic Education Bachelor’s program at a university in northern Portugal. The collected data correspond to the answers given by the students in a formal examination in a Probability and Statistics course. An analysis of the answers showed that the students had difficulties in both the selection and application of statistical methods, which were more pronounced when they had to identify the appropriate graphs to represent the data and to determine the quartiles and to interpret the third quartile, and less pronounced in the case of determining other statistical measures.